Streptococcus mutans carriage in the saliva of mothers and its association with dental caries and Streptococcus mutans carriage in the saliva of children between 6 and 30 months old in a low‐income setting in Karachi, Pakistan. Issue 6 (30th September 2022) - Nizar, Ambreen; Sheikh, Maheen; Khan, Farhan R.; Iqbal, Najeeha Talat; Azam, Syed I.; Qureshi, Shahida; Ali, Asad; Jehan, Fyezah
Abstract: Background: Early childhood caries poses a significant health issue in children under 6 years old. It is determined that Streptococcus mutans is a primary etiological agent, likely to be transferred through maternal contact. Objectives: To determine the association of maternal S. mutans counts with S. mutans counts in their children between 6 and 30 months of age, and to determine the maternal and child DMFT (decayed, missing, and filled teeth) indices. Material and Methods: A community‐based cross‐sectional study was conducted in Karachi, Pakistan. A sample of 193 dyads of mother–children (6–30 months of age) was selected via purposive sampling. Saliva samples of the dyads were collected to assess S. mutans count. Caries assessment was performed for both using the DMFT index. A pretested questionnaire was used. The association of bottle‐feeding, oral hygiene measures, and other factors with S. mutans counts in children were also explored. Zero‐inflated negative binomial regression model at a 5% level of significance was applied using STATA version 12.0. Results: Out of 193 children, 109 (56.47%) were males and 84 (43.52%) were females. The mean age of mothers and children was 29.4 ± 6.2 years and 19.54 ± 6.8 months, respectively. Maternal S. mutans counts were not statistically associated with child's S. mutans counts (Mean child's S. mutans count ratio: 1; 95% confidence interval [CI]: 1, 1.01; p  = .882). Compared with children who were breastfed, S. mutans counts were higher in children who were bottle‐fed (mean S. mutans count ratio= 4.85 [95% CI: 1.53, 15.41], p  = .007). Age of mother and present caries status of mothers was significantly associated with the child's S. mutans count. Conclusion: No association between maternal S. mutans and child S. mutans was observed. However, maternal age, children who were breastfed, children who did not use pacifiers,  and children with mothers who did not have caries, exhibited low S. mutans counts in their saliva. WHY THIS PAPER IS IMPORTANT: No association was observed between maternal S. mutans and child S. mutans count. Breastfeeding, pacifier use, increasing maternal age, and absence of maternal caries were linked to lower S. mutans counts in children.